2022
DOI: 10.1371/journal.pntd.0010118
|View full text |Cite
|
Sign up to set email alerts
|

Viral Parkinsonism: An underdiagnosed neurological complication of Dengue virus infection

Abstract: Dengue virus (DENV) is a flavivirus that is a significant cause of human disease costing billions of dollars per year in medical and mosquito control costs. It is estimated that up to 20% of DENV infections affect the brain. Incidence of DENV infections is increasing, which suggests more people are at risk of developing neurological complications. The most common neurological manifestations of DENV are encephalitis and encephalopathy, and movement disorders such as parkinsonism have been observed. Parkinsonism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Recently, a meta-analysis has shown that the development of parkinsonism may be an underdiagnosed complication of Dengue virus infection. However, also in this case, as for the other viruses mentioned above, there seems to be no data showing an association between an increased risk of developing idiopathic PD and a previous infection by Dengue virus (16). Antigenic mimicry has been hypothesized to explain the increased risk of PD after herpes simplex virus 1 (HSV-1) infection.…”
Section: Parkinson's Disease and Infectious Diseasesmentioning
confidence: 73%
“…Recently, a meta-analysis has shown that the development of parkinsonism may be an underdiagnosed complication of Dengue virus infection. However, also in this case, as for the other viruses mentioned above, there seems to be no data showing an association between an increased risk of developing idiopathic PD and a previous infection by Dengue virus (16). Antigenic mimicry has been hypothesized to explain the increased risk of PD after herpes simplex virus 1 (HSV-1) infection.…”
Section: Parkinson's Disease and Infectious Diseasesmentioning
confidence: 73%
“…Pathophysiology may be direct neuronal invasion or antibody-dependent enhancement [82]. Other syndromes described recently include Parkinsonism [83], myelitis [84] and GBS [85]. Laboratory diagnosis of acute dengue is by demonstration of NS1 antigen or IgM antibodies in serum (IgG can predominate in secondary infection), or by PCR in very early stages of the illness [86].…”
Section: Emerging Infections In the Tropicsmentioning
confidence: 99%
“…The CNS has a unique and complex structure with a restricted regeneration capacity. The perturbation of the CNS homeostasis, induction of neuroinflammation, neuronal damage, and neuron degeneration often occur as a result of a CNS viral infection and are closely associated with the development of neuroinflammatory and neurodegenerative diseases such as multiple sclerosis (MS) [ 6 , 7 , 8 , 9 , 10 , 11 ], Alzheimer’s [ 10 , 12 , 13 ], epilepsy [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], and others [ 26 , 27 , 28 , 29 , 30 ]. In fact, viral infections are known or suspected to play a role in the onset and progression of various neurological disorders.…”
Section: Introductionmentioning
confidence: 99%